THE EFFECT OF LI2O ONCOMPOSITE LTAP AND WINDOWS GLASSES - Bambang Prihandoko; Priyo Sardjono; Anne Zulfia; Eddy Siradj (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
THE EFFECT OF LI2O ONCOMPOSITE LTAP AND WINDOWS GLASSES. Research on The Effect of Li2O on Composite LTAP and Windows Glasses have been done. Windows glasses contain of SodiumLime Silica Glasses and Na2O 11,6%, CaO 8,1%and SiO2 58,7%. LTAP ( Lithium Titanium Alumunium Phosphate ) material mixed in the slurry of powder windows glasses with composition of weight procentage 75%. The temperatures process for sintering of samples is above of glass transition at 600 oC. Then samples quenched with liquid nitrogen. The variation of Li2O addition on samples are 0, 2,5, 5 and 7,5% weight. XRD pattern of all samples has a same phenomenon of crystallization phases, i.e. LTAP with lithium silica from Li5Si2O7, Li2SiO3, Li4SiO4 and Li2Si2O5. Optimum addition oh Li2O is 7,5% weight Li2O that gift a conductivity of 1,479 x 10-7 S/cm and high value on density and smallest porosity